DINAMIKA KELOMPOK TANI SARONGSONG YOUTH DI KELURAHAN TUMATANGTANG SATU, KECAMATAN TOMOHON SELATAN, KOTA TOMOHON - Charly ., Kojansow; Jenny ., Baroleh; Martha M. Sendow (Sam Ratulangi University, 2016)
This research aims to know the dynamics of farmer groups Sarongsong Youth in Tumatangtang One Vilage Sub-District South Tomohon. This research method was using study case. Data is taken from primary data and secondary data from February 2016 until April 2016, primary data was conducted with interview techniques using a list of questions while the secondary data were taken from the Office of Neighborhood, Office districts and local Office of Agricultural Extension, Fisheries and Forestry (BP3K). All members of the Group of farmers Sarongsong Youth Tumatangtang Villages One Sub-district South Tomohon became the source of the respondents in this study. Variable research includes the 8 (eight) factor is the dynamics of farmer groups, namely: the purpose of the group, group structure, group functions, the function of the coaching group, group cohesiveness, the atmosphere, the pressure group on a group of farmers, farmer groups and effectiveness. The data obtained in the analyses are descriptive, and the results obtained are presented in the form of a percentage of the Table. The research results showed that farmers group dynamics Sarongsong Youth in Tumatangtang Neighborhoods One Sub-district South Tomohon is a good category. This is especially shown by factors the dynamics of farmer groups in addition to the pressure on the group, which is due more to sub factor is still less. Farmers group dynamics Sarongsong Youth needs to be improved again, especially the factor of pressure on the group. Should be given its own awards to members of the other groups in order to provide more motivation for them is appropriate, especially when there are more who contribute to a group.